Connecting shear localization with the long-range correlated polarized stress fields in granular materials - Yinqiao Wang (Nature Portfolio, 2020)
Understanding the behavior of jammed granular matter is important for a range of phenomena, from materials science to geology. Wang et al. uncover relations between stress correlations and emergence of localized shear bands due to external shear stress, which breaks the rotational symmetry.